Situation Analysis of In-Service Teachers' Expertise of Teaching Literacy to Visually Impaired Students Using Braille - Dr. Muhammad Javed Aftab,; Dr. Rukhsana Bashir,; Dr. Hina Hadayat Ali,; Dr. Bushra Naz,; Kiran Shehzadi,; Fariha Iqbal, (Al-Qanṭara, 2023)
This study investigated in-service teachers' knowledge of utilising Braille and ability to teach Literacy to people with learning difficulties in this setting. Understanding the many types of information these instructors possessed was critical for understanding how they integrated distinct teacher' knowledges' in imparting literacy skills to visually impaired learners. The sample of the study comprised of 110 teachers of VI. Service instructors who were teaching visually impaired students were purposefully sampled. To explore how the participants processed their surroundings. The study design for this research is survey. The research is entirely quantitative. A survey is a versatile tool that may be used to gather information from a wide range of people. The research method requires that the data be either observational or experimental, or both. A survey is a method of gathering information from a larger population by having a small number of individuals participate. Participants appeared to teach Blind as a "standalone" topic, despite the fact that it is meant to also be linked with other disciplines as well as literacy instruction. This study has the potential to be reproduced in a larger region and in other circumstances. The study indicated that in-service instructors have poor expertise of various aspects of teaching reading to visually impaired pupils.